New World Postcolonial : The Political Thought of Inca Garcilaso de la Vega - Fuerst, James W. (James William) (Illuminations (Pittsburgh, Pa.), 2018)
New World Postcolonial presents the first full-length study to treat both parts of Inca Garcilaso de la Vega's foundational text Royal Commentaries of the Incas as a seminal work of political thought in the formation of the early Americas and the early-modern period. It is also among a handful of studies to explore the Commentaries as a "mestizo rhetoric," written to subtly address both native Andean readers and Hispano-Europeans. As Fuerst demonstrates, by blending both Andean and European discourses to represent Incan history, Garcilaso further proposed restoring indigenous sovereignty by adopting a new mestizo governing body via the political alliance and intermarriage of encomenderos (estate holders) and Incas. This policy extended to education, missionary practices, and others, reflecting Garcilaso's hopes of forming a peaceful coexistence among native Andeans, mestizos, and first generation Spaniards.